Effect of Lower Third Molar Status on Fracture of Mandibular Angle and Condyle - Muhammad Adil Asim ,Ayesha Maqsood , Fouzia Aslam , Anosha Mujtaba , Muhammad Adil Asim ,Ayesha Maqsood , Fouzia Aslam , Anosha Mujtaba (Journal of Rawalpindi Medical College, 2018)
Background:To determine the correlation between impacted M3 and mandibular angle and condylar fractures considering the hypothesis that the presence of M3s increases the risk of mandibular angle and simultaneously decreases the risk of condylar fracture and vice versa.. Methods: In this cohort study seventy-five patients having ninety-two hemi-mandibles with fracture of condylar process or angle were included. Status of third molar on the fractured side of mandible was determined. Based on status of mandibular third molars patients were broadly classified into two groups i.e. erupted and impacted. Results:Among the total 92 hemi-mandibles that were fractured, 56.5% had angle fractures while 43.5% had condylar fractures. Out of total 48 hemi-mandibles with impacted third molars, mandibular angle was fractured in 72.92%. While among 44 hemi-mandibles having erupted third molars, 61.36% had condylar fractures. Conclusion: Mandibular angle fractures more readily as the result of facial trauma in the presence of an impacted M3,especially with Class B depth and class 2 ramus position. Absence of an impacted mandibular third molar increases the risk of condylar fractures while concomitantly decreasing the risk of mandibular angle fracture.